Migration compensation algorithm for maneuvering target in passive radar based on FRT-MLVD - Yongsheng ZHAO; Dexiu HU; Ke JIN; Zhixin LIU; Yongjun ZHAO (Tongxin xuebao)
During the long coherent integration time in passive radar,the motion parameters (such as high speed,acceleration and jerk motion,etc.) will bring about range migration (RM) and Doppler frequency migration (DFM),further deteriorate the integration performance.To realize the coherent integration of maneuvering targets with jerk motion,a method based on frequency reversing transform (FRT) and modified Lv’s distribution (MLVD) called FRT-MLVD was proposed to achieve the coherent integration and motion parameters estimation.More specifically,the FRT was firstly proposed to remove RM.Then the MLVD was employed to estimate the acceleration and jerk parameters.After compensating the DFM induced by the acceleration and jerk motion,the residual RM was corrected and the velocity and range was achieved via the KT operation.Simulation results demonstrate that the proposed method can effectively compensate the RM and DFM induced by the target motion parameters in passive radar,and for maneuvering targets with jerk motion,the proposed method achieves a better integration and detection performance over existing methods.